Efektivitas Penerapan Sholat Subuh Berjamaah Di Mesjid Bagi Siswa Sekolah Dasar Di Kabupaten Mandailing Natal (Studi Kasus Peraturan Bupati No.12 Tahun 2022 Pasal 19 Ayat 1) - Nur Hakimah (Journal on Education, 2024)
The Congregational Dawn Prayer Program at the Mosque for elementary school students is one of the programs of the Regent of Mandailing Natal in 2022, namely Mr. Muhammad Jafar Sukhairi Nasution, where he issued Regent Regulation No. 12 of 2022 which was signed in Panyabungan on March 14, 2022, contained in Chapter V Article 19 paragraph 1 confirming the additional content of the Religious Education curriculum in educational units in the form of habits that practice and cultivate Islamic teachings through the implementation of Congregational Dawn Prayers for Elementary School Students (SD) throughout Mandailing Natal Regency. The results of the study that the author obtained regarding the effectiveness of the implementation of congregational dawn prayers in elementary school education units in Mandailing Natal Regency are that some villages have implemented it effectively with sustainability until now, this is because of strong support from the local government, while more in various villages have no longer implemented it effectively for various reasons. It can be concluded that the Regent Regulation should be very effective in improving the character of Elementary School students, but it is ineffective because it is not implemented seriously by the relevant parties for several reasons as explained. The purpose of this study is to see the effectiveness of the implementation of Regent Regulation Number 12 of 2022 Article 19 Paragraph 1 where elementary school students, especially boys, are required to add extracurricular religious activities by implementing congregational dawn prayers at the mosque.